Seismic Analysis of Multistorey Building on Sloping Ground Using NBC 105:2020 - Khatri , Abhinesh; Kafle, Shesh Raj; Kalathoki, Aarju; Dangol , Prashant; Yadav, Siddhartha; Oli, Sabitra; Rai , Saujan; Limbu, Anjal; Poudel, Alina; Ojha, Bimal (International Journal on Engineering Technology and Infrastructure Development, 2025)
The purpose of this study is to investigate the seismic behavior of RC buildings in steep or sloping terrain. It has been investigated how the structure responds dynamically in slope ground. Nearly seven distinct structural arrangements have been investigated. Three of them are step-back and set-back, three of them are step- back and one is Building on flat land. This structural configuration comprises buildings constructed at varying slope angles 0o (flat ground), 15o, 25o and 35o. The complete building configuration under consideration is stimulated using ETABS v22.0.0, and NBC 105:2020. The response spectrum is then analyzed using comparable static analysis methodologies. The buildings under consideration were then compared in terms of fundamental time period, top storey displacement, drift, and story stiffness. The seismic behavior of structures on flat ground differs from that of structures on steep terrain (sloping ground). The fundamental time period of vibration and base shear has decreased with increase in slope. However, higher slopes result in large stiffness variations across storeys, increasing the risk of torsional effects and soft-storey formation. The study shows that steeper slopes significantly reduce seismic base shear but introduce other structural challenges like torsional effects, irregular mass distribution, and local stress concentrations that should be carefully considered in design.